Mechanical behaviour of braided fibrous structures for artificial knee ligaments - Cruz, Juliana (2012)
One of the research trends explored within the last few years is the use of braided fibrous materials as artificial grafts as they offer the possibility to mimic the structure as well as mechanical behaviour of artificial ligaments. The present paper reports the development of a special type of braided structure using polyamide 6.6 fibres for applications as artificial ligaments. The developed structures were circular braids, axially reinforced with a number of core braided structures. Tensile behaviour of these structures was characterized and the influence of number of axial braids and the number of yarns used in the axial braids were thoroughly investigated and discussed. The results showed that the produced braided structures can mimic the load-elongation behaviour of natural ACLs. The breaking force showed linear increase with the number of axial braids as well as with the number of yarns in the axial braids. Therefore, there lies a huge possibility to reach the mechanical properties of natural ACL by adjusting these parameters since, these braided structures (0.6 mm) are much thinner in diameter than the natural ACLs (11 mm). Moreover, as polyamide fibres have similar mechanical behaviour as bicompatible fibres like polyglycolic acid, in future these structures can be developed with biocompatible fibres for better integration with the surrounding tissues.